2013
DOI: 10.1167/iovs.12-10250
|View full text |Cite
|
Sign up to set email alerts
|

A Cationic Peptide, TAT-Cd0, Inhibits Herpes Simplex Virus Type 1 Ocular Infection In Vivo

Abstract: PURPOSE.To test the in vivo activity of a peptide derived from the protein transducing domain of the human immunodeficiency virus (HIV) Tat protein, TAT-Cd 0 , in a murine herpes simplex type 1 (HSV-1) keratitis model. METHODS.The efficacy of TAT-Cd 0 was assessed in a postinfection treatment model with different concentrations (1 mg/mL, 0.1 mg/mL, 0.01 mg/mL) of the peptide in one of four delivery vehicles: artificial tears, PBS, methylcellulose, and aquaphor cream. Treatment began within 4 or 24 hours postin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Therefore, the knowledge of the viral genome, protein structure, replication cycle, and host cell targets is of great importance for the description of efficient inhibitors [23]. Interestingly, in some cases, a peptide designed to target a specific virus can be used as a template for the design of a new peptide against a different virus [130]. Viral surface glycoproteins are often a target, because they are essential in both the entry and penetration process, and require conformational changes given the protein-protein interaction which they undergo [23].…”
Section: Rationally Designed Avpsmentioning
confidence: 99%
“…Therefore, the knowledge of the viral genome, protein structure, replication cycle, and host cell targets is of great importance for the description of efficient inhibitors [23]. Interestingly, in some cases, a peptide designed to target a specific virus can be used as a template for the design of a new peptide against a different virus [130]. Viral surface glycoproteins are often a target, because they are essential in both the entry and penetration process, and require conformational changes given the protein-protein interaction which they undergo [23].…”
Section: Rationally Designed Avpsmentioning
confidence: 99%
“…7 Studies in other laboratories have also demonstrated the antiviral potential of highly cationic peptides. Jose et al 8 have shown the efficacy of a cationic peptide, TAT-CD 0 , which is able to inhibit HSV-1 ocular infection in vivo, and Brandt et al 9 have shown the antiviral efficacy of another highly cationic molecule, a modified theta defensin, RC-2, in a murine model of HSV-1 keratitis. With our own peptide work, we suggested that coupling an agent that inhibits viral entry with a nucleoside analogue, such as ACV, that inhibits viral replication, would target the viral infection in two distinct ways.…”
mentioning
confidence: 99%
“…31 We then tested the efficacy in a mouse model of herpetic keratitis using 4 different vehicles: PBS, 2% methylcellulose gel, artificial tears, and a cream. 46 We found, regardless of the formulation, that TAT-Cd o applied topically 5 times per day at a concentration of 1 mg/mL significantly reduced the severity of corneal vascularization and stromal keratitis. Treatment reduced viral shedding by 1.5 logs at 24 h postinfection.…”
Section: Peptides Derived From Proteinsmentioning
confidence: 65%